A phase I trial of mushroom powder in patients with biochemically recurrent prostate cancer: Roles of cytokines and myeloid‐derived suppressor cells for Agaricus bisporus–induced prostate‐specific antigen responses. Issue 17 (18th May 2015) - Twardowski, Przemyslaw; Kanaya, Noriko; Frankel, Paul; Synold, Timothy; Ruel, Christopher; Pal, Sumanta K.; Junqueira, Maribel; Prajapati, Manisha; Moore, Tina; Tryon, Pamela; Chen, Shiuan
<x xml:space="preserve">Abstract</x> BACKGROUND Each year in the United States, nearly 50, 000 prostate cancer patients exhibit a rise in prostate‐specific antigen (PSA) levels, which can indicate disease recurrence. For patients with biochemically recurrent prostate cancer, we evaluated the effects of white button mushroom (WBM) powder on serum PSA levels and determined the tolerability and biological activity of WBM. METHODS Patients with continuously rising PSA levels were enrolled in the study. Dose escalation was conducted in cohorts of 6; this ensured that no more than 1 patient per cohort experienced dose‐limiting toxicity (DLT). The primary objective was to evaluate treatment feasibility and associated toxicity. The secondary objectives were to determine WBM's effect on serum PSA/androgen levels; myeloid‐derived suppressor cells (MDSCs); and cytokine levels. RESULTS Thirty‐six patients were treated; no DLTs were encountered. The overall PSA response rate was 11%. Two patients receiving 8 and 14 g/d demonstrated complete response (CR): their PSA declined to undetectable levels that continued for 49 and 30 months. Two patients who received 8 and 12 g/d experienced partial response (PR). After 3 months of therapy, 13 (36%) patients experienced some PSA decrease below baseline. Patients with CR and PR demonstrated higher levels of baseline interleukin‐15 than nonresponders; for this group, we observed therapy‐associated declines in MDSCs. CONCLUSIONS Therapy with WBM appears to both impact PSA levels and modulate the biology of biochemically recurrent prostate cancer by decreasing immunosuppressive factors. Cancer 2015;121:2942–2950. © 2015 American Cancer Society.